KUALIFIKASI TINDAKAN PEMUTUSAN SUPLAI AIR DAN LISTRIK TERHADAP WARGA PALESTINA DALAM PERSPEKTIF HUKUM HUMANITER : QUALIFICATION OF WATER AND ELECTRICITY CUT-OFF MEASURES AGAINST PALESTINIANS IN THE PERSPECTIVE OF HUMANITARIAN LAW - Hidayat, Nadia Angelica; Abdullah, Fero Sayid; Zuhra, Amalia (terAs Law Review : Jurnal Hukum Humaniter dan HAM, 2022)
The hostilities between Israel and Palestine is are escalating in 2023. It started with Hamas attacking Israel on October 7th, 2023. It led Israel to attack the Palestine, especially Gaza Strip with strikes. Not long after, the Government of Israel then ordered the Israeli companies to cut off water and electricity to Palestine. This action lead to several impacts on Palestinians, particularly civilians who do not participate in the hostilities. The action of cutting water and electricity are violating the principle of distinction, principle of precautionary, principle of unnecessary injuries, and principle of necessity.